STRATEGI PARTAI POLITIK DALAM PEMILIHAN LEGISLATIF TAHUN 2014 (STUDI KASUS PDI PERJUANGAN DI DAPIL II KECAMATAN RUMBAI DAN RUMBAI PESISIR KOTA PEKANBARU) - Afdhal, Said; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study on the legislative elections of 2014 ago, an increase of votes is very significant that experienced by the PDI-P in the City Pekanabru. This is seen in the comparison sounds PDI obtained in 2009 which won 11 551 votes, while in 2014 the PDI-P, said Monday that 30 374 voice sound. the author is trying to formulate questions such as "how the PDI-P strategy in recruiting legislative pemelihan pemillih in 2014 in Dapil II District Rumbai and Rumbai Coastal. The purpose of this study to mengetahuai strategy undertaken by the PDI-P in recruiting voters on the legislative elections 2014. On the results of research and discussion of trying to define all mutual researcher in two classifications at the level of analysis that is offensive strategy PDI Pekanbaru city, then the analysis is based on the strategy Defensive Indonesian Democratic Party struggle Pekanbaru. This research method approach this research uses qualitative that can be interpreted as the research that produced the data Descriptive, location research was conducted in the city of Pekanbaru precisely at the Council Office Pimpingan Branch Party PDI Pekanbaru, tekni pengumpula data in this study are: Interviews then Documentation after data writers get, for data analysis techniques, as follows: Presentation of Data Reduction the data is then include various types namely matarik, tables, and charts network. Based on the research and the strategies used Branch Council party PDI-P Pekanbaru in increasing the vote on the legislative elections of 2014 the city of Pekanbaru do Retkrutmen is open for prospective Legislature, then the Son Branch PDI help celeg to socialize under pantawan Board PDI Branch Pimpimnan struggle Pekanbaru. Keywords: Strategy Indonesian Democratic Party of Struggle, Election Legislative In 2014, the city of Pekanbaru.